A Tangible Head Model for Physical Treatment of Benign Paroxysmal Positional Vertigo. (2nd September 2014) - Fujisaka, Michiro; Shojaku, Hideo
Abstract : Objectives: In this study, we developed a tangible head model for the physical treatment of benign paroxysmal positional vertigo (BPPV) and assessed the educational efficacy of this model for people. This model has a 10‐time‐scale mockup of the semicircular canal, which contains 10 canalith particles, located in a 1.5‐time‐scale mockup of the head. Methods: This was a prospective study involving 20 medical students just starting to study otolaryngology. At first, they learned the canalith repositioning procedure (CRP) from an article. After reading the article, they tried to move 10 canalith particles from the ampulla to the utricle using the model, during which they were not able to see inside. Second, they practiced the CRP using the model, and they could see the inside. Third, they tried to move 10 canalith particles from the ampulla to the utricle using the model, during which they could not see the inside. Compare the number of canalith particles, which students can move from the ampulla to the utricle, before and after practice using the model. Results: Before practice using the model, they could move 2.5 (mean value) canalith particles, after practice, they could move 6.6 (mean value) canalith particles. There was a statistical difference ( P <. 01) between trials before and after practice using the model. Conclusions: It was suggested that a tangible head model for the physical treatment for BPPV is a useful educational tool for people such as resident doctors, medical students, and patients with BPPV.